PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA MELALUI MODEL THINK PAIR SHARE BERBANTUAN MEDIA STICK MULTIPLICATION - Ria Anggraeni; Puji Rahmawati; Tria Mardiana; Sumardi (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2023)
The low ability of students to solve a problem greatly influences student learning outcomes. Problem solving abilities can be influenced by the learning process they experience. One of them is the lack of use of models and media to carry out learning. The TPS learning model assisted by Stick Multiplication media is an alternative that teachers can use to overcome students' low problem-solving abilities in the Mathematics subject, multiplication material. Researchers used classroom action research (PTK) as a research approach. The subjects used in this research were 27 students in class IVA at SD Negeri Depok 1. Researchers use observation, test and documentation techniques to collect data. The observation data obtained in cycle I was 60% and increased in cycle II by 85%. Meanwhile, the average test score data obtained in cycle I was 73.07%. Then the researchers made improvements in cycle II and the results increased to 86.29%. So the researcher concluded that research using the TPS learning model assisted by Stick Multiplication media could improve the ability to solve mathematical problems on multiplication material in class IVA students at SD Negeri Depok 1. Keyword: Mathematic Problem Solving Abilities, Model TPS, Learning Activities